Faraway suture technique in hypospadias repair - Ahmed E Lasheen (Journal of Surgery and Surgical Research - Peertechz Publications, 2020)
Background: The complications after hypospadias repair still occurred in spite of much advancement of type of suture materials and suture techniques. This study offers new suture technique trying to improve the outcome of hypospadias repair. Methods: This study included 23 hypospadias cases (11 distal penile, 7 mid penile, 5 proximal penile hypospadias). The standard Tabularized Incised Plate (TIP) technique was used in all cases, but the suture technique is faraway, where the two suture limbs passed under the urethral edges. Every suture was tied faraway of urethral edges by about 1cm on one side. Then, the penile skin closed as usual. Lasheen urethral stent was used for two weeks. The mean follow up period was 12months.  Results: The Suture is transverse mattress, the distance between its limbs and every suture was about 3mm. when these sutures were tied bring more soft tissue in midline and inversion urethral plate edges inside the urethra. Healing period was 2 weeks. No urethra-cutaneous fistula or meatal stenosis or penile curvature were noticed during period of follow up. Conclusion: Faraway suture technique in hypospadias repair is easy , has short learning curve, and associated with good physiological urethra and penile anatomy.